Pencegahan Stunting Sejak Dini di Era Milenial Desa Sukokerto Kecamatan Pajarakan Kabupaten Probolinggo - Indro Wicaksono (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas Panca Marga Probolinggo, 2019)
Most people do not understand correctly about Stunting, and assume that Stunting or dwarf designation commonly used in society is heredity. This dedication activity is carried out to increase knowledge and understanding of stunting which is expected to directly motivate the community to participate in paying attention to the growth and development of their children so that their growth and development can be optimal. Factors causing stunting are low birth weight, not getting exclusive breastfeeding, lack of energy and protein intake, and not immunizing. Based on statistical data on the progress of the implementation of the acceleration of prevention of integrated stunting in East Java Province, the status of April 2019, Probolinggo district, showed that the prevalence of stunting reached 94%, the data of stunting children in 2018 reached 17.29%. Data from the analysis of the stunting prevention plan in Probolinggo Regency in 2020 through a source from Bappeda Sukokerto village, including villages with 90 children under five. Data stunting in the village of Sukokerto was 3.72%. The main target of the implementation of the socialization program on prevention of stunting is pregnant women and children under five in the Sukokerto village community by holding a Posyandu Outreach event with the theme